Analisis Geologi dan Sebaran Batubara Seam X Daerah Gurimbang, Kabupaten Berau - Permana, Aang Panji; Saida, Muhammad Syaifullah; Muhammad Kasim, Muhammad Kasim; Asmoro, Yoki Dwi (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
Coal is a fossil energy source that is widely available in the world, including Indonesia. Indonesia is one of the ten largest coal producing countries in the world. One area that has coal reserves is Berau Regency, East Kalimantan Province. The research location is in the concession area of PT. Berau Coal which covers the Binungan, Lati, Sambarata, Birang, Punan, Kelai, Gurimbang and Parapatan areas. Administratively, the research location is located south of Gurimbang Village, Sambaliung District, Berau Regency, East Kalimantan Province. The aim of this research is to analyze the geological conditions and distribution of Seam X coal in the North Gurimbang area, Berau Regency. To achieve this goal, methods are used, namely activities in the field and studio. Activities in the field include collecting data on the position of rocks through field geological surveys. Field geological surveys are to determine the geological conditions of the research area in the form of the constituent rocks, stratigraphic relationships, factors that form morphology and geological structure. Activities in the studio involve analyzing subsurface data. The results and discussion show that the geomorphology of the research area is divided into three geomorphic sub-units, namely swamp plains, denudational hills and mine openings sub-units. The stratigraphy of the study area is grouped into three informal rock units, in order from old to young as follows: sandstone units, mudstone units and alluvial deposit units. The distribution of the seam The distribution pattern of seam